Purification of amorphous boron powder by using the soluble transformation of acid-insoluble boron magnesium compounds - Lv S.-X.; Cao Z.; Wu J.-J. (Journal of Mining and Metallurgy. Section B: Metallurgy)
At present, amorphous boron powder is considered to be the best fuel for solid fuel-rich propellants due to its extremely high volume calorific value and mass calorific value. Amorphous boron powder produced by magnesium thermal reduction contains many impurities that are insoluble in acids as well as defects such as low purity, excessive particle size, and poor chemical activity, which seriously hinder its large-scale application in the military and aerospace fields. In this paper, the soluble transformation mechanism of insoluble boron magnesium compounds into amorphous boron powder during calcination and a method for purification boron powder were studied. In order to remove insoluble boron magnesium compounds in amorphous boron powder, the insoluble impurities Mg5B2O5 and MgB4 were converted into soluble MgB4O7 and MgO during calcination. The samples were then subjected to either water leaching or acid leaching to convert the crude amorphous boron powder products into high-purity amorphous boron powder products. SEM-EDS, XRD, XPS, and other techniques were used to determine the occurrence states of the impurity phases. The transformation of impurity phases after calcining water leaching and acid leaching was monitored. The results showed that the magnesium content in the amorphous boron powder was reduced to 0.96%, and the purity of the boron powder was increased to 97.34% by subjecting the amorphous boron powder to a combined calcination technique and either water leaching or acid leaching treatment.